2021
DOI: 10.3390/biology10070621
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptin Increases Antioxidant Expression in the Kidney, Liver and Brain of Diabetic Rats

Abstract: Nociceptin (NC) consists of 17 amino acids (aa) and takes part in the processing of learning and memory. The role of NC in the induction of endogenous antioxidants in still unclear. We examined the effect of NC on the expression of endogenous antioxidants in kidney, liver, cerebral cortex (CC), and hippocampus after the onset of diabetes mellitus, using enzyme-linked immunosorbent assay and immunohistochemistry. Exogenous NC (aa chain 1–17; 10 µg/kg body weight) was given intraperitoneally to normal and diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…NOP agonism regulates the activity of neurons within these sites affecting the activity of several other neurotransmitters involved in feeding regulation. Moreover, considering the important commonalities between eating disorders and drug abuse [ 203 , 204 , 205 ] and the role of the N/OFQ-NOP system in the modulation of motivated behaviors (see paragraphs above), it is conceivable that the function of the N/OFQ-NOP system is not limited to the metabolic regulation of feeding and in the induction of endogenous antioxidants under certain conditions, such as diabetes mellitus [ 206 ]. Indeed, it plays a role in the motivation for food, possibly contributing to the etiopathology of eating disorders.…”
Section: Role Of the N/ofq-nop System In The Regulation Of Feeding And Food-related Disordersmentioning
confidence: 99%
“…NOP agonism regulates the activity of neurons within these sites affecting the activity of several other neurotransmitters involved in feeding regulation. Moreover, considering the important commonalities between eating disorders and drug abuse [ 203 , 204 , 205 ] and the role of the N/OFQ-NOP system in the modulation of motivated behaviors (see paragraphs above), it is conceivable that the function of the N/OFQ-NOP system is not limited to the metabolic regulation of feeding and in the induction of endogenous antioxidants under certain conditions, such as diabetes mellitus [ 206 ]. Indeed, it plays a role in the motivation for food, possibly contributing to the etiopathology of eating disorders.…”
Section: Role Of the N/ofq-nop System In The Regulation Of Feeding And Food-related Disordersmentioning
confidence: 99%
“… 27 , 28 , 29 In kidney tissue, NOP has been implicated to exert direct renal effects by downregulating aquaporin-2-mediated water reabsorption and inducing endogenous antioxidants-associated nephroprotection. 30 , 31 Furthermore, preclinical and pilot clinical studies also elucidated that the NOP receptor agonist, SER100 (Serodus, ASA, Oslo, Norway), induced vasodilatation, promoted diuresis, and decreased BP, partially through their orchestration of autonomic tone and locally prejunctional inhibition of noradrenergic neurotransmission. 32 , 33 As for N/OFQ, it is ubiquitously expressed throughout the central nervous system, especially in brain regions involved in autonomic and cardiovascular control.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in SOD activity could be a possible coping response due to the excessive production of ROS that occurs with diabetes. However, a few researchers also reported on lower SOD activity in diabetes [24,[63][64][65][66]. Chou & Tseng, in 2017, [67] demonstrated that there were no differences in SOD activity among the three groups in type-2 diabetes patients with diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%